Diversity of dinoflagellates in the sea off Mangalore - Mendon, Mridula R; Katti, R J; Rajesh, K M; Rajesh, T R C (Indian Journal of Fisheries, 2011)
The spatial and temporal distribution of dinoflagellates in the ArabianSea off Mangalore was studied for eight months (October 1997 to May1998). Six genera of dinoflagellates such as Ceratium, Peridinium,Preperidinium, Dinophysis, Diplopsalis and Gonyaulax were recorded.Dinoflagellates occurred throughout the period of study with distincttemporal and spatial variations. Among the dinoflagellates observed,Ceratium and Peridinium were more dominant followed by Dinophysis,Diplopsalis and Gonyaulax.